Application of generalized linear models to data analysis in drinking water treatment (2005)
In drinking water treatment we found appropriate linear models to explain dose and concentration of sulphate, dose of lime, lime application probability and polymer application probability, including as explanatory variables some physical and chemical properties of raw water.